International law - Henriksen, Anders (Oxford, United Kingdom : Oxford University Press, 2019)
International Law presents a student-focused approach to the subject; clearly written with non-native English-speaking students in mind, a range of learning features highlight the areas of debate and encourage students to engage critically with key disputes.
Foundations and structure of international law -- Sources of international law -- The law of treaties -- The actors in the international legal system -- Jurisdiction -- Immunity from national jurisdiction and diplomatic protection -- State responsibility -- The international law of the sea -- International human rights law -- International environmental law -- International economic law -- The peaceful settlement of disputes -- The international regulation of the use of force -- The law of armed conflict -- International criminal law.
Previous edition : 2017.
Includes bibliographical references and index.
Keywords: International law